Theorising Web 3.0: ICTs in a changing society. Issue 4 (2nd November 2015) - Kreps, David; Kimppa, Kai
Abstract : Purpose: – The purpose of this paper is to analyse the broad phases of web development: the read-only Web 1.0, the read-write Web 2.0, and the collaborative and Internet of Things Web 3.0, are examined for the theoretical lenses through which they have been understood and critiqued. Design/methodology/approach: – This is a conceptual piece, in the tradition of drawing on theorising from outside the Information Systems field, to shed light on developments in information communication technologies (ICTs). Findings: – Along with a summary of approaches to Webs 1.0 and 2.0, the authors contend that a more complex and poststructuralist theoretical approach to the notion of, and the phenomenon of Web 3.0, offers a more interesting and appropriate theoretical grounding for understanding its particularities. Originality/value: – The discussion presages five further papers engaged with ICTs in a changing society, each of which similarly addresses novel theoretical understandings.